Russian Federation : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2011)
Even though the Russian authorities have maintained financial stability at the time of a major global shock, the financial system is still weak. The crisis has set back progress toward a strong, competitive banking system for the future. The recent unification of the supervision of nonbank financial institutions is an opportunity for strengthened oversight. A more structured corrective action regime and a unified administration regime for all banks, with broad powers for the administrator, would help strengthen the system further.